Bone lipogranuloma mimicking metastatic disease on 18F-FDG PET/CT - DEDE, FUAT (My University, 2023)
Primary bone lipogranuloma is an extremely rare disease associated with reactive inflammatory granulomatous reaction associated with exogenous or endogenous lipids. Herein, we report a case of bone lipogranuloma with intense 18F-FDG uptake, which mimics metastatic disease on 18F-FDG PET/CT in a patient with breast cancer.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; 18F-FDG PET/CT; bone lipogranuloma; breast cancer; lipogranuloma; metastasis